Evaluation of Radio Frequency Identification (RFID) technology as a tracking instrument in the supply chain of pharmaceutical products with a case study at ZLB Behring GmbH - Fischer, Thorsten (2005)
The pharmaceutical industry is commonly referenced as one of the first adopters using RFID technology in a large scale to gain operational efficiencies in the supply chain and to protect its products against counterfeiting. It seems that the initial hype around RFID has moved from the retail sector (e.g. Wal-Mart) to the pharmaceutical and health care industry.